Designing Performance Tasks in Mathematics Using Technological Tools - De Las Peñas, Ma. Louise Antonette N (Archīum Ateneo, 2021)
In the Philippines, the performance task is one of the major summative assessments in the K to 12 curriculum. This paper discusses how performance tasks may utilize mathematical apps within the context of blended learning. Guidelines on designing performance tasks; as well as the GRASPS framework; are discussed. Performance tasks that cut across various grade levels and strands of mathematics are presented. These involve divisibility (Numbers); integer and polynomial operations (Algebra); triangle centers (Geometry); and statistics (Statistics). The performance tasks described in this paper can provide an initial idea for the design of other summative assessments and contribute to the literature on the use of technological tools in assessment and evaluation.